Spanish verb drills - Bey, Vivienne; Concheff, Beatrice Jorgensen; Yates, Jean (Verb drills, 2022)
"Build mastery in Spanish verbs for confident communication! An essential foundation for learning Spanish is confidence in the use of its verbs. Spanish Verb Drills will help you overcome difficulties and lay the foundation for effective communication through clear explanations and rigourous practice. Your language skills will be strengthened as you become more fluent in your use of the correct tenses and verb forms"--Back cover.